The Metaphor of Love in the Treatise of Ṭawq Al-Ḥamāmah by Ibn Ḥazm Al-Andalusiy (Semantic and Cultural Analysis) - Pebriawati, Tri Wahyuni; El Qorny, Ashief (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2025)
This study examines the metaphor of love in the treatise Ṭawq al-Ḥamāmah by Ibn Ḥazm al-Andalusiy using semantic and cultural approaches. The goal is to identify the types of semantic fields of love metaphors based on Michael C. Haley's theory, explain the relationship of metaphors with Arab-Andalusian culture, and interpret Ibn Ḥazm's concept of love as depicted in his metaphorical expressions. This research is qualitative with descriptive-analytical methods and library research types. The primary data is in the text of Ṭawq al-Ḥamāmah, while the secondary data includes linguistic literature, metaphors, and classical Arabic culture. The analysis is carried out through documentation techniques, symbolic and semantic readings, and metaphor classification based on semantic field theory and cultural metaphors. The study results show eight categories of semantic fields, with the dominance of being, object, and human, and the strong influence of Andalusian culture on the construction of metaphorical meaning. According to Ibn Ḥazm, love is understood paradoxically, spiritually, abstractly, transcendently, and procedurally.